A regional integrated energy system with a coal-fired CHP plant, screw turbine and solar thermal utilization: Scenarios for China. (15th May 2020) - Liu, Haochen; Geng, Zhi; Gu, Yujiong; Mo, Ziyuan; Yu, Zhiwen; He, Xuehao; Lu, Shuyin
Highlights: A high-efficient pressure matcher was proposed, validated and analyzed in Ebsilon. Low-stent-placed steam supply pipeline module was furtherly investigated and used to transport steam within 4 km. A steam-driven screw turbine was introduced to satisfy an eco-industrial park's electric and heat need. Solar thermal utilization part was used to pre-heat domestic water with taking Beijing and Huzhou's DNI into consideration. Energy, exergy and entransy analysis was simultaneously considered to analyze main equipment in regional system. Abstract: Regional integrated energy system has been a suitable scheme in China to satisfy eco-industrial park's both electric and heat needs. Combined heat and power (CHP) is an efficient technology for coal-fired plants during heating seasons. Currently, wires transport electric from CHP to destination while urban pipes network transport heat from CHP to destination, respectively. However, this might not be the case in future, when eco-industrial parks are close to plants or pipes network can't carry enough heat. This paper presents a feasible regional integrated energy system which meets both electric and heat's needs with steam from CHP while maintaining photothermal resources' high percent utilization. This system includes a coal-fired CHP plant, pressure matcher, steam supply pipeline, screw turbine and solar thermal utilization part. This paper set up a model of 600 MW electric power CHP with pressure matcher and screw turbine in Ebsilon software. Then the steam supply pipeline and solar thermal utilization part were developed and analyzed based on the basic thermodynamic theories with Beijing and Huzhou's meteorological statistics taken into consideration. Besides, the operational issues of the regional system were also listed. Meanwhile, the regional integrated energy system was obtained and a lot of characteristics were analyzed. Main devices were further investigated with energy, exergy and entransy analysis. Three extreme working situations were also carried out and discussed in the end. Several useful conclusions were drawn. It's necessary for China to masterly integrate regional energy system with multi-energy. Moreover, pressure matcher is high-efficient in general under other parameters' influences. This extracting steam's technology might be considered in future. Besides, low-stent placed pipeline which can transport high-parameter steam 4 km at most was introduced. A proper mass flow value or lower inlet temperature will both reduce loss of pipeline. Furthermore, heat user side can offer electric power about 9.22 MW, heating acreage about 0.79 km 2 to the eco-industrial park. More solar heat's import, lower upper temperature difference and less sunlight will favor solar thermal utilization part. Higher heat load or lower CHP's working condition will benefit screw turbine. Peak heat exchanger doesn't need to work when supply domestic water temperature's demand is less than 65 °C. The simulation in this paper might give technological statistics to the regional integrated energy system which has CHP and photothermal. This will help to put this energy system into actual use in future.